Surviving the sanctuary city : asylum-seeking work in Nepali New York - Shrestha, Tina (University of Washington Press, 2023)
"Surviving the Sanctuary City asks what everyday survival among migrants and asylum seekers can tell us about the cultural logic of suffering within the confines of US borders"-- Provided by publisher.
Keywords: New York (N.Y.) -- Social conditions -- 21st century.; Nepali people -- New York (State) -- New York.; Marginality, Social -- New York (State) -- New York.; Part-time employment -- New York (State) -- New York.; Népalais -- New York (État) -- New York.; POLITICAL SCIENCE.; Asian American Studies.; Ethnic Studies.; SOCIAL SCIENCE.; Anthropology.; Marginality, Social; Nepali people; Part-time employment; Social conditions; New York (State) -- New York; 2000-2099; Electronic books.